Transcriptional memory in skeletal muscle. Don't forget (to) exercise. Issue 7 (22nd January 2020) - Beiter, Thomas; Nieß, Andreas M.; Moser, Dirk
Abstract: Transcriptional memory describes an ancient and highly conserved form of cellular learning that enables cells to benefit from recent experience by retaining a mitotically inheritable but reversible memory of the initial transcriptional response when encountering an environmental or physiological stimulus. Herein, we will review recent progress made in the understanding of how cells can make use of diverse constituents of the epigenetic toolbox to retain a transcriptional memory of past states and perturbations. Specifically, we will outline how these mechanisms will help to improve our understanding of skeletal muscle plasticity in health and disease. We describe the epigenetic road map that allows skeletal muscle fibers to navigate through training‐induced adaptation processes, and how epigenetic memory marks can preserve an autobiographical history of lifestyle behavior changes, pathological challenges, and aging. We will further consider some key findings in the field of exercise epigenomics to emphasize major challenges when interpreting dynamic changes in the chromatin landscape in response to acute exercise and training. Abstract : Transcriptional memory is a highly conserved strategy of cells to qualitatively adapt gene expression responses by integrating signals with recent and remote experience. Transcriptional memory mechanisms enable the skeletal muscle to navigate through the process of exercise‐induced adaptation and determine skeletal muscle plasticity in health and disease.